Anatomical Position of Four Different Transobturator Mesh Implants for Female Anterior Prolapse Repair - Lenz, F.; Doll, S.; Sohn, C.; Brocker, K. A. (Geburtshilfe und Frauenheilkunde, 2013)
Purpose: Polypropylene mesh implants are frequently used for pelvic floor reconstruction in women. Yet they vary in size and fixation. The purpose of this study is to compare four mesh products with regard to their anatomical positioning and functionality within the pelvic floor, to determine whether each mesh fits equally well in a female cadaver. Methods: One female pelvis was dissected, opening the retropubic space exposing the endopelvic fascia and demonstrating the arcus tendineus fasciae pelvis (ATFP). Anatomical parameters were measured before and after implanting four meshes via the transobturator approach. Results: The anterior fixation of the ATFP was found to be 5 mm lateral to the symphysis in this cadaver. The endopelvic fascia covered 54.6 cm2. The obturator nerve was located 35 mm from the white line. The distance of the proximal and lateral points of mesh fixation from the ischial spine or ATFP varied from 0 to 25 mm. The meshes varied in size and anatomical positioning. Conclusion: These observations demonstrate the necessity of developing optimally sized meshes and appropriate introducer techniques that can provide sufficient vaginal support. Surgeons, furthermore, need profound knowledge of anatomy, the patientʼs pelvic floor defect and the meshes available on the market.
Keywords: mesh repair; arcus tendineus fasciae pelvis; white line; endopelvic fascia; pelvic floor anatomy